2021
DOI: 10.1021/acs.biomac.1c00425
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of Macrophage-Target Nanoparticles by Yeast Microparticles for Rhein Delivery in Ulcerative Colitis Treatment

Abstract: In this study, we developed an advanced colitis-targeted nanoparticles (NPs)-into-yeast cell wall microparticles (YPs) drug delivery system for ulcerative colitis (UC) therapy. In brief, YPs entrap hyaluronic acid (HA), and polyethylenimine (PEI) modified rhein (RH)-loaded ovalbumin NPs (HA/PEI-RH NPs) to form HA/PEI-RH NYPs. YPs can make HA/PEI-RH NPs pass through gastric environment stably and be degraded by β-glucanase to promote drug release from HA/PEI-RH NYPs in the colon. Cellular uptake evaluation conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 41 publications
0
29
0
1
Order By: Relevance
“…The maximum dose of Rhein in this study was significantly lower than that in Yang's study (Jones‐Hall et al, 2015). On the other hand, nano‐drug delivery system was reported to have advantages of increase in target distribution of drugs in the lesions and decrease in the non‐target distribution in other organs from the perspective of pharmaceutics (Chen et al, 2021; Luo et al, 2021). Hence, a nano‐drug delivery system for oral delivery of Rhein has the potential to become a novel and safety strategy for the treatment of UC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum dose of Rhein in this study was significantly lower than that in Yang's study (Jones‐Hall et al, 2015). On the other hand, nano‐drug delivery system was reported to have advantages of increase in target distribution of drugs in the lesions and decrease in the non‐target distribution in other organs from the perspective of pharmaceutics (Chen et al, 2021; Luo et al, 2021). Hence, a nano‐drug delivery system for oral delivery of Rhein has the potential to become a novel and safety strategy for the treatment of UC.…”
Section: Discussionmentioning
confidence: 99%
“…Anthraquinones have been recognized as the active compounds of Rhei Radix et Rhizoma. In our existing study, Rhein, one of the main anthraquinones, was reported to exert anti‐UC effect by regulating the NF‐κB signaling pathway (Chen et al, 2021). However, whether Rhein could regulate the PI3K/Akt/mTOR signaling pathway in UC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, as its pathogenesis is complex, including the interaction of host response and gene and immune influence caused by exogenous substances, 8 the therapeutic outcomes are greatly limited. 9 Moreover, these agents are apt to result in some unpredictable side-effects 10 including cardiac complications 11 and non-asthmatic eosinophilic bronchitis. 12 Nowadays, epidemiological investigations suggest that some functional foods such as green tea, coffee, polysaccharides 69 and yogurt possessing antioxidant, anti-inflammatory and gut microbiota regulation properties exhibit prevention capability for UC.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our preliminary research and previous relevant experimental research, RH has been shown to have multiple therapeutic effects on UC . Indeed, the available evidence indicates that RH can alleviate UC symptoms by regulating multiple inflammatory pathways (including TLR4/MyD 88 /NF-κB, and PI3K/Akt/mTOR signaling pathway). , In particular, the TLR4/NF-κB pathway is a key signaling pathway involved in colon inflammation . Meanwhile, some studies have shown that RH can alleviate symptoms of UC by activating the Nrf2/HO-1-mediated oxidative stress pathway .…”
Section: Introductionmentioning
confidence: 86%
“…Next, the RH release profiles from RH-F/C-NPs were examined using a dialysis method. 10 Briefly, 3 mL RH-F/C-NPs and free RH (RH concentration: 45 μg/mL) were added to separate the dialysis bags (MWCO 3000, Millipore). Meanwhile, Tween-80 (1% (w/v)) was supplemented into the releasing medium to maintain the RH solubility in the aqueous phase.…”
Section: Ph/ros Dual Sensitivity and Releasementioning
confidence: 99%